Declining trend in anemia prevalence among non-pregnant women of reproductive age in Vietnam over two decades: A systematic review and meta-analysis of population studies - Nguyen Trung Kien; Tran Quang Duc; Vu Thi Quynh Chi; Phan Ngoc Quang; Bui Thi Thanh Tuyen; Dinh Thi Phuong Hoa (Tabriz University of Medical Sciences, 2022)
Background: Anaemia is a public health concern in developing nations, particularly among women of reproductive age. However, the present prevalence and recent trend in anaemia among this population are unclear. This systematic review aimed to evaluate the prevalence of anaemia among non-pregnant women in Vietnam. Methods: We systematically searched databases such as PubMed, Scopus, and reference lists of earlier prevalence studies from their inception until July 2022. For statistical analysis to check for heterogeneity, random or fixed effects models were employed to summarize the prevalence of anaemia. Visual examination of a funnel plot was used to determine the presence of publication bias, which was then verified using the Egger regression test. Subgroup analyses were also undertaken to evaluate how the proportion of anaemia differs across various study groups. Results: A total of 188 studies were found as a result of the bibliographical search. Finally, of the 12 included studies, anaemia affected 5089 non-pregnant women out of a total of 19744, making the prevalence of this condition 23.2% (95% CI: 16.1-32.2). From 1995 to 2013, the prevalence of anaemia in this population declined significantly, from 42.6% to 16.9%. Notably, the prevalence of anaemia among non-pregnant women differed by geography and increased by mountains, Northern Vietnam, rural areas, and ethnic minority groups. Furthermore, no publication bias was found in this meta-analysis. Conclusion: To enhance the health of women and meet global objectives for eliminating anaemia, more efforts are required in specific regions and ethnic minority groups in Vietnam.